2019
DOI: 10.1002/jcp.28898
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐ATB promotes TGF‐β‐induced glioma cells invasion through NF‐κB and P38/MAPK pathway

Abstract: Glioma constitutes the most aggressive primary intracranial malignancy in adults. We previously showed that long noncoding RNA activated by TGF-β (lncRNA-ATB) promoted the glioma cells invasion. However, whether lncRNA-ATB is involved in TGF-β-mediated invasion of glioma cells remains unknown. In this study, quantitative real-time polymerase chain reaction and western blot analysis were used for detecting the mRNA and protein expression of related genes, respectively. Transwell assay was performed to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…For instance, lncRNA-ATB could promote the proliferation, migration and invasion of cervical cancer or glioma. 13,19 Our current study further confirmed these results, suggesting that lncRNA-ATB could act as an oncogene. In addition, our study firstly found that lncRNA-ATB played a critical role in the tumorigenesis of ovarian cancer, which supplemented the biological function of lncRNA-ATB.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, lncRNA-ATB could promote the proliferation, migration and invasion of cervical cancer or glioma. 13,19 Our current study further confirmed these results, suggesting that lncRNA-ATB could act as an oncogene. In addition, our study firstly found that lncRNA-ATB played a critical role in the tumorigenesis of ovarian cancer, which supplemented the biological function of lncRNA-ATB.…”
Section: Discussionsupporting
confidence: 85%
“…10 Previous studies have indicated that lncRNA-ATB could significantly promote the progression of multiple malignancies. [11][12][13] However, the role of lncRNA-ATB in the progression of ovarian cancer remains to be explored. Thus, this research aimed to explore the biological function of lncRNA-ATB during the progression of ovarian cancer in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that ATB acts as a competing RNA by binding with microRNA (miR)-494 in lung cancer cells (28), miR-141-3p in gastric cancer cells (29), miR-590-5p in melanoma (30), and miR-200 family members in diverse types of cancer (18,26,31,32). ATB regulates transcriptional coactivator YAP1 (YAP1), NF-κB, p38 mitogen-activated protein kinase (MAPK), Twist, and TGF-β in lung cancer, glioma, breast cancer and malignant melanoma (23,30,33,34). In hepatic fibrosis, ATB knockdown downregulated β-catenin expression by upregulating the expression of endogenous miR-200a (35).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-ATB induced EMT and promoted metastasis of HCC cell lines by sponging miR-200 family [16]. The role of lncRNA-ATB was also investigated in other cancer cell lines, such as prostate cancer [17], glioma [18], cervical cancer [19] and breast cancer [20]. However, the value of lncRNA-ATB in clinical practice of NSCLC is unknown.…”
Section: Discussionmentioning
confidence: 99%